Interdomain B in ZAP-70 Regulates but Is Not Required for ZAP-70 Signaling Function in Lymphocytes - Zhao, Qihong (American Society for Microbiology, 1999)
The protein tyrosine kinase ZAP-70 plays an important role in T-cell activation and development. After T-cell receptor stimulation, ZAP-70 associates with the receptor and is phosphorylated on many tyrosines, including Y292, Y315, and Y319 within interdomain B. Previously, we demonstrated that Y292 negatively regulates ZAP-70 function and that Y315 positively regulates ZAP-70 function by interacting with Vav. Recent studies have suggested that Y319 also positively regulate ZAP-70 function. Paradoxically, removal of interdomain B (to create the construct designated Δ), containing the Y292, Y315, and Y319 sites, did not eliminate the ability of ZAP-70 to induce multiple gene reporters in Syk-deficient DT-40 B cells and ZAP-70/Syk-deficient Jurkat cells. Here we show that Δ still utilizes the same pathways as wild-type ZAP-70 to mediate NF-AT induction. This is manifested by the ability of Δ to restore induction of calcium fluxes and mitogen-activated protein kinase activation and by the ability of dominant negative Ras and FK506 to block the induction of NF-AT activity mediated by Δ. Biochemically we show that the stimulated tyrosine phosphorylation of Vav, Shc, and ZAP-70 itself is diminished, whereas that of Slp-76 is increased in cells reconstituted with Δ. Deletion of interdomain B did not affect the ability of ZAP-70 to bind to the receptor. The in vitro kinase activity of ZAP-70 lacking interdomain B was markedly reduced, but the kinase activity was still required for the protein’s in vivo activity. Based on these data, we concluded that interdomain B regulates but is not required for ZAP-70 signaling function leading to cellular responses.